PEMIKIRAN EPISTIMOLOGI ABID AL-JABIRI DAN IMPLIKASINYA BAGI DINAMIKA KEILMUAN ISLAM - Titian Ayu Naw Tika (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Epistemological issues are fundamental in scientific discourses, including Islamic scholarship. The pattern of epistemology will determine the character of the science it produces. Abid Al-Jabiri through his criticism of Arabic reasoning has clearly demonstrated the types of epistemology that have been used in Islamic scientific disciplines since its formative era. This study aims to explain the various types of epistemology and their methodological patterns that have existed in Islamic scientific disciplines since their formative period and their relevance to the dynamics of Islamic scholarship today. Methodically this research uses two stages of research, namely collecting data related to research and then analyzing the data that has been collected. In general, the authors find that the problems of Islamic scholarship today are strongly influenced by the disposition between the three types of epistemology that have been formulated by Abid Al-Jabiri, namely burhani, bayani, and irfani.